Effect of heat and heat acclimatization on cycling time trial performance and pacing - Racinais, S.; Périard, J.; Karlsen, A. (Medicine & Science in Sports & Exercise, 2015)
Purpose: This study aimed to determine the effects of heat acclimatization on performance and pacing during outdoor cycling time trials (TT, 43.4 km) in the heat.